Efektivitas Pelayanan Publik Berbasis Aplikasi Layanan Moci Legit Di Dinas Kependudukan Dan Pencatatan Sipil Kota Sukabumi - Ayu Andriani; Ike Rachmawati; Tuah Nur (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
In today's digital era, every public service provider is required to provide services more quickly to provide satisfaction for the community as service recipients. Therefore, Sukabumi City Disdukcapil has innovated services from offline to online through the Moci Legit Service application, this is done to provide convenience to the community so that the service process is more effective and efficient, but in its implementation there are several phenomena of problems found, namely: 1.not yet optimal socialization carried out, 2.the application system often experiences trouble, 3. inaccuracy of document completion, 4.there is no complaint feature in the application. This study aims to determine how the effectiveness of public services based on the legitimate moci service application at the Population and Civil Registration Office of Sukabumi City. The theory used in this study is the effectiveness theory from Gibson and Steers which includes 5 dimensions: productivity, quality, efficiency, flexibility, and satisfaction. The method used in this research is descriptive qualitative. The results of this study indicate that the dimensions of productivity, quality, efficiency, and satisfaction are considered not fully effective because there are things that need to be improved to be more optimal. While the flexibility dimension is considered to have been running effectively.